(3JMaI GdWdGH HTQM fRgI GdMSGHs - (3YeQ Hf Ydj Hf CMeO GdCfUGQj GdTGaYj, SQGL GdOjf, CHh MaU GHf GdfMhj, GdeYQha HGHf Gdedbf, J (B804 (3g` s; (3TgGH GdOjf CMeO Hf eMeO Hf YeGO GdOjf Hf Ydj GdefUhQj GdSdej, GHf GdgGFe,J (B815 (3g` s
(3ChdgG (B:s
(3hHYO abO cfJ ai MGd GdWahdjI hGdTHGH ETJZdJ HYde GdaQGFV hGdMSGH s
(3BNQgG (B:s
(3hJZjQ GdCMhGd hcKQI Gdbjd hGdbGd bGd ai GdCUd hdYd ef GdfGSN Je GdcJGH HMeO Gddg s
(3GdfSNI HgG MhGTs
(3fRgI GdMSGH GfXQ cTa GdXfhf L(B2 (3U` (B1942s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B226s
Keywords: (3GdQjGVjGJs